A new genus of Proterotheriinae (Mammalia, Litopterna) from the Pleistocene of Uruguay. Issue 1 (2nd January 2019) - Corona, Andrea; Perea, Daniel; Ubilla, Martín
ABSTRACT: We describe a new genus and species of Proterotheriinae from the Pleistocene of Uruguay. Several taxonomic, biostratigraphic, paleoecological, and paleoenvironmental analyses and interpretations have been performed in a detailed study of the Litopterna (Mammalia, 'Meridiungulata') of Uruguay. The Proterotheriidae is the most diverse family of the Litopterna. In Uruguay, the record of the Proterotheriidae, although in many cases fragmentary, includes interesting specimens in particular contexts and different ages in the late Oligocene–late Pleistocene. The aim of this work is to reassess the specimens primarily assigned four decades ago to ' Licaphrium ' aff. floweri, redescribing them, evaluating their taxonomic status in the context of the Proterotheriidae, and establishing the characters that allow the determination of this taxon as a new genus and species of Proterotheriinae: Uruguayodon alius . We redescribe two specimens of this new taxon, which include dental and postcranial remains. The diagnostic element is the last lower molar, which shows, among other characters, paraconid and paralophid in a very lingual position, smoothed metaflexid, and absence of entoflexid. The individuals were excavated from a sandy level of the San José Member of the Raigón Formation, a unit that has an endemic fauna, a pattern discussed here in a paleogeographic framework. The provenance of the analyzed specimens from Pleistocene layers is indicated by mammalian content and absolute ages, which support the presence of another genus of Proterotheriidae surviving into the Quaternary, in addition to Neolicaphrium recens .